Sustainability Report Quality: Media and Shareholder Effect - Suroso, Dian Ma'rifatul Maqfiroh; Kholilah (Politeknik Piksi Ganesha Indonesia, 2024)
The research objective is to examine the effect of social media, media coverage, shareholders on the quality of sustainability reports. Measurement of social media variables from the number of likes, comments, tweets on facebook, instagram, twitter. media coverage from the number of negative issues on the detik and kompas websites. shareholders from the largest percentage of share ownership. quality of sustainability reports through the 2016 GRI index. The research population is public companies in the Consumer Non Cyclicals sector, using purposive sampling technique in determining the sample obtained 53 companies. Technical data analysis using multiple linear regression. The results of the study are social media, media coverage, shareholders have no effect on the quality of sustainability reports. the findings show limited utilization of social media by 53 sample companies for sustainability, so that differences in research samples can be the cause of different influences with previous studies.